Influence of Electrohydrodynamics on the Drying Characteristics and Volatile Components of Ginger - Jie Zhu; Changjiang Ding; Chuanqiang Che; Liqiang Liu; Junjun Lian; Zhiqing Song; Chunxu Qin (Applied Sciences)
This article studies the electrohydrodynamic drying of ginger. In this work, drying experiments were performed in an electrohydrodynamic drying (EHD) system at various AC voltages (0 kV (control), 15 kV, 20 kV, 25 kV, and 30 kV). The drying properties and volatile components of ginger were thoroughly examined and studied using IR spectroscopy and GC–MS. The findings revealed that electrohydrodynamics significantly increased the drying rate and reduced the drying time of ginger, with a sevenfold increase in drying rate and a one-third reduction in drying time at 30 kV. The peak of the infrared spectrum of ginger remains unchanged. We found 240 volatile chemicals under different drying voltages. The primary volatile chemicals were esters and aldehydes. The ginger products dried at 30 kV had the lowest aldehyde concentration. These findings give an experimental and theoretical foundation for applying electrohydrodynamics to the subject of ginger drying.